Item Response Theory: An Introduction to Latent Trait Models to Test and Item Development - Ado Abdu Bichi; Rohaya Talib (International Journal of Evaluation and Research in Education (IJERE), 2018)
Testing in educational system perform a number of functions, the results from a test can be used to make a number of decisions in education. It is therefore well accepted in the education literature that, testing is an important element of education. To effectively utilize the tests in educational policies and quality assurance its validity and reliability estimates are necessary. There are two generally acceptable frameworks used in evaluating the quality of test in educational and psychological measurements, these are; Classical Test Theory (CTT) and Item Response Theory (IRT). The estimates of test items validity and reliability depend on a particular measurement model used. It is vital for a test developer to be familiar with the different test development and item analysis methods in order to facilitate the development of a new test. The CTT is a traditional approach which was widely criticise in the measurement community for its shortcomings such as sample dependency of coefficient measures and estimates of measurement error. However, the IRT is a modern approach which provides solutions to most of the CTT’s identified shortcomings. This paper therefore, provides a comprehensive overview of the IRT and its procedures as applied to test item development and analysis. The paper concludes with some suggestions for test developers and test specialists at all levels to adopt IRT for its identified crucial theoretical and empirical gains over CTT. IRT based parameter estimates should be superior and reliable than CTT based parameter estimates. With these features, IRT can help resolve the problems associated with test design based on CTT.